Ecological, taxonomic and zoogeographic structure of complex of invasive phytophagous arthropods in green stands in Grodno Poneman Region - Hliakouskaya, Katsiaryna I.; Zhorov, Dmitrii G.; Ryzhaya, Alexandra V.; Buga, Sergej V. (Journal of the Belarusian State University. Ecology, 2019)
Biological diversity of alien phytophagous Arthropods includes 38 species of insects and mites which damaging decorative woody plants in green stands in Grodno Poneman region. There are representative 30 genera, 11 families and 9 superfamilies of insects (Insecta s.str. or Ectognatha) and Arachnids (Arachnida). They include 6 species of gall forming mites (Acariformes: Eriophyidae), 23 species of aphids (Sternorrhyncha: Aphidoidea & Phylloxeroidea) and 1 species of gall midge (Diptera: Cecidomyiidae), 1 species of scale insects (Sternorrhyncha: Coccoidea), 1 species of jumping lice (Sternorrhyncha: Psylloidea) and 1 species of thrips (Thysanoptera: Thripidae), 3 species of leaf mining moths (Lepidoptera: Gracillariidae). The majority of these alien species have European and Mediterranean (16 species) or North American (10 species) origin. Overwintering stages of Gracillariidae are imago and pupae, gall forming mites and mealybugs (Sternorrhyncha: Coccidae) – larvae of jumping plant lice and holocyclic aphids – ovae.
Keywords: Belarus; biological invasions; dendrocolous Arthropods; alien species; fauna